PENGEMBANGAN MODEL BELAJAR MENGAJAR MATA PELAJARAN IPS SD UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM BERBASIS KOMPETENSI DI PROPINSI SUMATERA SELATAN - Esti Hayu Purnamaningsih; Asmadi Alsa; Amitya Kumara (Faculty of Psychology, Universitas Gadjah Mada, 2004)
This research aimed to understand: 1) Could The Teachers apply the learning models that maked condusive learning situation so could be implementation media for competence based curriculum 2) were the learning models maked the joyfull learning, stimulated activity and creativity, and stimulated life-skills for students. 3) were the learning models fasilated integration two or more subject maters. The participant of the study were 160 students 4 teachers and head of shcools from the 3rd and 4th SD 17 and SD 23 Kayu Agung, Ogan Komering Ilir; and from the fifth SD Kertapati and SD Plaju Palembang, South Sumatera. The reasearh procedure were followed: 1) Socialitation about the learning models for Teachers, Head of Schools and School supervisors. 2) Teachers were aplied the learning models at the each class. 3) Monitoring aplicability learning models by researher and school supervisor. 4) semi-structured interviewed from researcher to teachers and studets. The Data was analysed with qualitative method. The result showed: 1) The Teachers could apply The Concept Analysis Model, Experiential Learning Model, and the Group Inquary Model that make condusive learning situation and could be implementation media for Competent based curriculum. 2) Applicability the Learning Models make joyfull learning, stimulated activity and creativity, and stimulated life-skills for students. 3) The learning models fasilated integration the IPS with Bahasa Indonesia and PPKn. Keyword: The Competent based Curriculum